Effectiveness Of Promotion, Price, Product Quality On Purchase Decisions With Purchase Interest As An Intervening Variable (Case study of CV. Agus Dharmawan Laksana Purwodadi) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the influence of promotion, price, and product quality on purchase decisions with purchase intention as an intervening variable, using a case study of Honda motorcycle consumers at CV. Agus Dharmawan Laksana Purwodadi. The method used is SEM-PLS with SmartPLS version 3.2.9 and purposive sampling technique. The results show that promotion has no significant effect on purchase intention or purchase decision. Price and product quality significantly influence purchase intention, but only product quality directly affects purchase decision. Purchase intention does not influence purchase decision and does not mediate the relationship between the variables. These findings indicate that consumers tend to consider product quality directly when making purchasing decisions.
Keywords: Promotion; Price; Product Quality On Purchase Decisions; Purchase Interest